1984
DOI: 10.1016/s0022-5347(17)50840-x
|View full text |Cite
|
Sign up to set email alerts
|

Further Characterization of the External Urethral Sphincter in Spinal Cord Injury: Study during Spinal Shock and Evolution of Responsiveness to Alpha-Adrenergic Stimulation

Abstract: To shed further insight into its ever evolving concepts, we studied the activity of the external urethral sphincter in patients with spinal cord injury. Study during the phase of acute spinal shock revealed persistent electromyographic activity in the external urethral sphincter and no activity in the external anal sphincter, suggesting the presence of functional dissociation between the 2 sphincters from the onset of acute spinal injury. The genesis of dissociated activity was discussed by reference to recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This is due mostly to a spinal reflex, given that it survives spinal cord injury even acutely in rats (27,38) and humans (18,24), and in that setting is presumably the basis for simultaneous contractions of bladder and EUS (bladder-sphincter dyssynergia). The pathway controlling this spinal tonic EUS reflex is schematized in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is due mostly to a spinal reflex, given that it survives spinal cord injury even acutely in rats (27,38) and humans (18,24), and in that setting is presumably the basis for simultaneous contractions of bladder and EUS (bladder-sphincter dyssynergia). The pathway controlling this spinal tonic EUS reflex is schematized in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On pres sure profile study the urethra responded supersensitively to both a-adrenergic stimulation and sitting posture with a rise in the max imal pressure of 22 and 26 mm Hg, respectively, while there was no change to parasympathetic stimulation. On sphincter EMG the EUS was absolutely silent and no change was evoked after a-adrenergic stimulation [14]. There was no opening of the vesical neck on void ing cystourethrography.…”
Section: Discussionmentioning
confidence: 87%
“…5). Conjoining these data and the recent experimen tal study by Elbadawi and Atta [29], who convincingly demonstrated autonomic reinnervation and even hyper innervation of rhabdosphincter (EUS) following its so matic denervation by bilateral sacral ventral rhizotomy, the phenomenon of a-activation of the EUS whose mo tor efferents are deranged would not be an enigma any more [14,30],…”
mentioning
confidence: 77%
See 2 more Smart Citations